2016
DOI: 10.1007/s10482-016-0730-5
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacteria possessing antimicrobial and antioxidant activities isolated from the pollen of scots pine (Pinus sylvestris) grown on the Baikal shore

Abstract: Isolated ecosystems existing under specific environmental conditions have been shown to be promising sources of new strains of actinobacteria. The taiga forest of Baikal Siberia has not been well studied, and its actinobacterial population remains uncharacterized. The proximity between the huge water mass of Lake Baikal and high mountain ranges influences the structure and diversity of the plant world in Siberia. Here, we report the isolation of eighteen actinobacterial strains from male cones of Scots pine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…We estimated their similarity with other actinobacteria and performed initial description of crude extracts antibiotic activity of bacteria cultivated in different nutrient media. According to the materials obtained in this study, we could preliminarily conclude that diversity of cultivable actinobacteria and rare genera isolated from D. baicalensis is comparable to that of cultivable actinobacteria that we previously isolated from the pollen of a pine species growing on the shore of the lake [29]. At the same time, according to published data, the diversity of rare genera of cultivable actinobacteria isolated here from the alga exceeds the cultivable actinobacteria diversity described for Lake Baikal macroinvertebrates [32,43], water [44,45], or sediments [46,47] (Figure 5).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We estimated their similarity with other actinobacteria and performed initial description of crude extracts antibiotic activity of bacteria cultivated in different nutrient media. According to the materials obtained in this study, we could preliminarily conclude that diversity of cultivable actinobacteria and rare genera isolated from D. baicalensis is comparable to that of cultivable actinobacteria that we previously isolated from the pollen of a pine species growing on the shore of the lake [29]. At the same time, according to published data, the diversity of rare genera of cultivable actinobacteria isolated here from the alga exceeds the cultivable actinobacteria diversity described for Lake Baikal macroinvertebrates [32,43], water [44,45], or sediments [46,47] (Figure 5).…”
Section: Discussionsupporting
confidence: 66%
“…In Baikal region, there were only single studies focused on assessment of cultivated actinobacteria diversity in high-plant communities. Thus, in one of the recent studies conducted by Axenov-Gribanov et al [ 29 ], a variety of actinobacteria in Pinus sylvestris pollen was estimated. The authors showed that the taiga forest of Baikal Siberia has not been well studied, and its actinobacteria population remains undescribed.…”
Section: Introductionmentioning
confidence: 99%
“…Some Amycolatopsis spp. have antimicrobial and antifungal activities (Saito et al, 2009 ; Axenov-Gribanov et al, 2016 ), which may explain the positive correlation of this bacterium with canola yield in our experiment. Another OTU related to a commonly observed endophyte, Pedobacter sp., was detected in the roots of canola and wheat in our experiment.…”
Section: Discussionmentioning
confidence: 52%
“…Endophytism was reported in several Amycolatopsis spp. (Miao et al, 2011 ; Xing et al, 2013 ; Klykleung et al, 2015 ; Axenov-Gribanov et al, 2016 ), and accordingly, an OTU related to Amycolatopsis sp. was detected only in the roots of canola in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that phenolic compounds exhibit a number of biological activities including antioxidant and antibacterial [64,65]. There is also evidence demonstrating that antioxidative compounds exhibit promising anti-MRSA activity [66][67][68].…”
Section: Discussionmentioning
confidence: 99%